Phylogeny and dating of divergences within the genus Thymallus (Salmonidae: Thymallinae) using complete mitochondrial genomes. (2nd September 2016) - Ma, Bo; Jiang, Haiying; Sun, Peng; Chen, Jinping; Li, Linmiao; Zhang, Xiujuan; Yuan, Lihong
Abstract: The genus Thymallus has attracted increasing attention in recent years because of its sharp demographic decline. In this study, we reported four complete mitochondrial genomes in the Thymallus genus: Baikal-Lena grayling ( T. arcticus baicalolenensis ), lower Amur grayling ( T. tugarinae ), Yalu grayling ( T. a. yaluensis ), and Mongolian grayling ( T. brevirostris ). The total length of the four new grayling mtDNAs ranged from 16 658 to 16 663 bp, all of which contained 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. The results suggested that mitochondrial genomes could be a powerful marker for resolving the phylogeny within Thymallinae. Our study validated that the Yalu grayling should be a synonym of the Amur grayling ( T. grubii ) at the whole mitogenome level. The phylogenetic and dating analyses placed the Amur grayling at the deepest divergence node within Thymallus, diverging at ∼14.95 Ma. The lower Amur grayling diverged at the next deepest node (∼12.14 Ma). This was followed by T. thymallus, which diverged at ∼9.27 Ma. The Mongolian grayling and the ancestor of the sister species, T. arcticus and T. arcticus baicalolenensis, diverged at ∼7.79 Ma, with T. arcticus and T. arcticus baicalolenensis separating at ∼6.64 Ma. Our study provides far better resolution of the phylogenetic relationships and divergence dates of graylings than previous studies.